Comparison of the Core Concepts, Historical Context, and Modern Scientific Evaluation of Darwin’s Theory of Natural Selection of Use and Disuse - Shen, Jiayi (International Journal of Public Health and Medical Research, 2025)
Charles Darwin’s theory of natural selection stands as the cornerstone of modern biology. Yet, its formulation and reception occurred against the backdrop of pre-existing evolutionary ideas, most notably Jean-Baptiste Lamarck’s theory of the inheritance of acquired characteristics, often summarized as "use and disuse." This paper provides a comprehensive comparison of these two pivotal theories, examining their core concepts, historical contexts, and crucially, their evaluation in light of modern science. We detail Lamarck’s vision of organisms actively adapting through use and disuse of organs, passing these modifications directly to offspring. We contrast this with Darwin’s mechanism of natural selection, where heritable variation within populations is acted upon by environmental pressures, leading to differential survival and reproduction. The historical analysis explores the intellectual climate of the 18th and 19th centuries, the influence of Lamarck on Darwin’s thinking, and the fierce debates surrounding the publication of On the Origin of Species. Modern scientific evaluation, grounded in genetics, molecular biology, and rigorous experimentation, overwhelmingly supports the core tenets of natural selection as the primary driver of adaptation and evolutionary change. While Lamarckian inheritance, as originally conceived, has been falsified, the paper explores nuances such as epigenetic inheritance and phenotypic plasticity, demonstrating how they differ fundamentally from Lamarckism while enriching our understanding of organism-environment interactions. Ultimately, this comparison highlights the revolutionary nature of Darwin’s theory, its enduring explanatory power, and why Lamarck’s "use and disuse," despite its historical importance and intuitive appeal, remains relegated to the annals of superseded scientific ideas, save for very specific and limited modern reinterpretations.